2011
DOI: 10.1007/s00442-011-2037-6
|View full text |Cite
|
Sign up to set email alerts
|

Towards a systemic metabolic signature of the arbuscular mycorrhizal interaction

Abstract: Our experiments addressed systemic metabolic effects in above-ground plant tissue as part of the plant's response to the arbuscular mycorrhizal (AM) interaction. Due to the physiology of this interaction, we expected effects in the areas of plant mineral nutrition, carbon allocation and stress-related metabolism, but also a notable dependence of respective metabolic changes on environmental conditions and on plant developmental programs. To assess these issues, we analyzed metabolite profiles from mycorrhizal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
53
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 36 publications
8
53
0
Order By: Relevance
“…Means across standardised data of identified compounds suggested that soil inoculation with AMF alone decreased concentrations of low molecular weight compounds in roots, particularly AA and saturated FA&E. Similar results were found by [49] for Lotus japonicus grown with or without AM fungi under different conditions. Information about the effects of AMF on the root metabolome is scarce.…”
Section: Discussionsupporting
confidence: 80%
“…Means across standardised data of identified compounds suggested that soil inoculation with AMF alone decreased concentrations of low molecular weight compounds in roots, particularly AA and saturated FA&E. Similar results were found by [49] for Lotus japonicus grown with or without AM fungi under different conditions. Information about the effects of AMF on the root metabolome is scarce.…”
Section: Discussionsupporting
confidence: 80%
“…Volcano plots 48 including all metabolic features of a given plant species with fold changes (mean intensity in mycorrhizal plants divided by mean intensity in control plants, presented on a log 2 scale for symmetry) were plotted in MATLAB (7.10.0.499; The MathWorks, Natick, MA, USA). To take into account that multiple testing may influence the results, all metabolic features had to pass two thresholds, namely unadjusted P valueso0.05 (Mann-Whitney U-tests) as well as a fold change o0.67 (corresponding too À 0.58 on a log 2 scale) for a decrease in metabolite pool size or 41.5 (40.58 on a log 2 scale) for an increase in metabolite pool size to be considered as modulated by AM, according to Fester et al 6 These thresholds were set with unadjusted P values, since adjustments (which are also given) are highly conservative due to the large numbers of metabolic features (see above). For each species, a w 2 -test was performed to test whether the number of decreased and increased features differed from a uniform distribution.…”
Section: Methodsmentioning
confidence: 99%
“…However, most knowledge on modulation considering a substantial set of metabolites relies on studies of few model plant species (for example, Arabidopsis thaliana 5 , Lotus spec. 6,7 , Medicago truncatula 8 , Plantago spec. 4,9,10 ) and the transferability of findings from these models to other plant systems is debatable.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…3 The most prominent changes are visible in the catabolic and amino acid metabolism, probably due to the improved carbon sink strength and an improved P-and N-level. 4 However, not only P and N, but also S provided by the symbiotic uptake pathway leads to changes in the metabolic response. 5 The recent identification of M. truncatula mutants defective in the symbiotic transfer of nutrients across the periarbuscular space allows us now to study the impact of fungal colonization independent of the improved nutrition of the plant.…”
Section: Resultsmentioning
confidence: 99%